Targeting hepatic macrophages for non-alcoholic fatty liver disease therapy - Tian, Yingxin; Ni, Yiming; Zhang, Ting; Cao, Yemin; Zhou, Mingmei; Zhao, Cheng (Frontiers in Cell and Developmental Biology, 2024)
Non-alcoholic fatty liver disease (NAFLD) and its more advanced form, non-alcoholic steatohepatitis (NASH), have become global health challenges with significant morbidity and mortality rates. NAFLD encompasses several liver diseases, ranging from simple steatosis to more severe inflammatory and fibrotic forms. Ultimately, this can lead to liver cirrhosis and hepatocellular carcinoma. The intricate role of hepatic macrophages, particularly Kupffer cells (KCs) and monocyte-derived macrophages (MoMFs), in the pathogenesis of NAFLD and NASH, has received increasing attention. Hepatic macrophages can interact with hepatocytes, hepatic stellate cells, and endothelial cells, playing a crucial role in maintaining homeostasis. Paradoxically, they also participate in the pathogenesis of some liver diseases. This review highlights the fundamental role of hepatic macrophages in the pathogenesis of NAFLD and NASH, emphasizing their plasticity and contribution to inflammation and fibrosis, and hopes to provide ideas for subsequent experimental research and clinical treatment.